Sistem Infomasi Geografis Pemetaan Persebaran UMKM di Kota Semarang - Wulan Agustina; Bambang Agus Herlambang; Ahmad Khoirul Anam (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Growth of Micro, Small and Medium Enterprises (UMKM) has become one of the important indicators in measuring the economic progress of a region. The research is aimed at conducting an analysis of the spread of UMKM in Semarang City using the Geographical Information System (GIS). This method allows the integration of geographical data with UMKM information, so that it can provide a more comprehensive picture of the number of UMK in different regions in semarang City. The Geographic Information System is used to mapp and analyze the patterns of the distribution of UMKL in Semang City. This study uses data that covers the location of the UMKM, and the number. The spatial analysis will provide insight into the diversity of UMM in different districts or regions. This Geographic Information System approach makes an important contribution to data visualization and interpretation